Editorial - Lämmerer, Anita; Mercer, Sarah (Studies in Second Language Learning and Teaching, 2019)
This collection of papers has emerged from the Language Education across Borders conference held at the University of Graz, Austria in 2017 (see also Kostoulas, 2019). In the age of translanguaging, multilingualism, multiculturalism, globalization, international migration, transnationalism, and the blending of content and language education, there is an ever greater need in language education to reflect on the interconnections and overlap between languages, disciplines, constructs, and contexts that have traditionally been conceptualized in bounded ways. Instead, professional and personal domains have got increasingly permeable boundaries leading to emergent qualities that require new ways of theorizing, researching and teaching. The idea behind the conference was to promote interdisciplinary exchange and encourage people to challenge the notions of borders of all kinds. The aim was to promote discourse and exchange and re-think the fragmentation and separation imposed by borders – real or imagined. It was hoped that by prompting people to reflect on the kinds of borders that bound their research and practice, we would be challenged to think outside of these borders and find the rich, creative space that can lead to innovation and fresh perspectives on the familiar.